The Role of Teachers in Implementing Mutual Cooperation Dimension P5 on the Merdeka Curriculum in Elementary Schools - Rahayu, Resta Indah; Kaltsum, Honest Ummi (Universitas Muhammadiyah Surakarta, 2023)
Purpose: There are 3 objectives of this research, namely: 1) analyzing the role of teachers in implementing the Pancasila student profile through the Mutual cooperation dimension in the Merdeka Curriculum; 2) explaining the efforts made by teachers to foster students' Mutual cooperation attitudes; and 3) mentioning the obstacles faced by teachers implementation of the P5 through the Mutual cooperation. Methodology: This type of research is qualitative phenomenology. Data collection techniques include interviews, observation, and documentation. Data validity is carried out by triangulating sources and techniques. Data analysis includes data collection, data reduction, data presentation, verification, and drawing conclusions. Results: The research results show that 1) the teacher's role in implementing the Mutual cooperation dimension is carried out by carrying out activities during and outside of learning. When learning, the teacher plays a role in holding the P5 project by carrying out group work, and when outside of learning, the teacher forms class pickets, divides students into ceremonial officers, picks up catering by students, accompanies students to decorate the class, and holds Clean Friday and morning alms; 2) the teacher's efforts to foster an attitude of Mutual cooperation, namely by habituating and always reminding students; 3) the obstacles faced by teachers are differences in student character and problems at times. Applications/Originality/Value: This research reveals that teachers have a role to foster students' mutual cooperation during learning and outside of learning in elementary schools.